How should we measure global poverty in a changing world? - Lars Osberg; Kuan Xu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Before effective anti-poverty policy can be designed and implemented, the extent, trend and distribution of poverty must be identified. In this sense, poverty measurement is a crucial intermediate step in public policymaking and development planning. This paper asks whether the estimated proportion of the world's population with income below US1 (adjusted according to purchasing power parity) per day is a good measure of trends in global poverty. We argue that the answer depends on two important issues in the measurement of poverty—the definition of the poverty line, and how best to summarize the level of poverty In this paper, we survey the literature on poverty measurement, demonstrate the importance of considering poverty incidence, depth and inequality jointly, present a simple but powerful graphical representation of the Sen and SST indices of poverty intensity (the poverty box) which is the FGT index of order 1 and extend our empirical work to China using the commonly accepted international poverty line definition of one half median equivalent income. – development ; poverty ; measurement ; China ; rural ; urban
Keywords: O15; I32; 330; Armut; Messung